Elaboración de un manual de procedimientos de control interno para inventarios de mercaderías en la empresa "Mega centro el éxito" año 2011 - Varela Guerra, Javier Lenin (2012)
The draft manual drafting internal control procedures for inventories of goods in the company "Mega Success Center" in 2011, begins with the diagnosis of the activities related to the process of inventory control, data collection and analysis allowed detect flaws in the process of inventory management, organizational structure and the internal and external forces that the company owns, which made the development of suitable procedures manual. Based on the diagnosis made to defined procedures described in the manual. The procedures are identified, the purchase and payment of goods, income, custody, Expenses and merchandise sales, deepened in the analysis of such procedures, this information for the development of the manual. After developing the manual, we defined the characteristics, such as design. Among the benefits obtained with the manual may be mentioned, possession of an administrative tool for the induction of new workers and consultation for older workers. The procedures manual allows updates on the purchasing process, storage and dispatch of goods for sale, generating new working methods to increase productivity and business efficiency. This manual is made based on the Laws, Rules and Regulations governing the country today. Theoretical information has been compiled from various literature sources that are within reach today. (Books, internet, brochures, delivered by teachers).